ANALYSIS OF THE MECHANISM FOR DETERMINING PROFITS ON GOLD INSTALMENTS AT BANK MUAMALAT’S BANDA ACEH ACCORDING TO THE MURABAHAH AGREEMENT - Syarifah Insyirah Mahzain; Dedy Sumardi (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This study aims to analyse the determination of profit margins in gold instalment financing at the Bank Muamalat Banda Aceh Branch under the murabahah contract. Gold instalment financing has become one of the leading products of Islamic banking because it provides easy access to gold ownership through an instalment mechanism. Still, it raises questions about the nature of the profit margins banks apply. In murabahah contracts, profit margins are part of the selling price that must be agreed upon at the outset of the contract and cannot be positioned as compensation for the use of time. Problems arise when financing margins are linked to the instalment period and are perceived by some customers as part of the instalment system. This study uses a qualitative, normative-empirical approach, reviewing the provisions of the murabahah contract in the DSN-MUI fatwa and sharia economic law literature, and collecting empirical data through interviews and observations. The study shows that the profit margin in gold instalment financing is determined and agreed upon from the outset of the contract and is included in the gold’s selling price. However, there are still differences in customers’ understanding of the margin’s position in the contract structure. This study concludes that, normatively, the determination of the margin is consistent with the murabahah contract. Still, a deeper understanding of the contract is needed so that financing practices continue to reflect the characteristics of sharia-compliant buying and selling.